Effect of Fuel Subsidy Removal on the Nigerian Economy: Implications for Households in Nigeria - ADDAH, Grace A (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study examined the impact of fuel subsidy removal on the Nigerian economy, with particular emphasis on food prices, standard of living, and poverty levels among citizens. Methodology: A survey research design was adopted. Primary data were collected through structured questionnaires and interviews administered to selected respondents. Descriptive analytical techniques were used to assess the socio-economic effects of subsidy removal. Results: The findings revealed that fuel subsidy removal has significantly increased food prices, leading to higher costs of basic commodities. It also negatively affected the standard of living, as households faced increased financial pressure and declining purchasing power. Findings: The study established that subsidy removal ha contributed to rising poverty levels by increasing the overall cost of living. Sectors such as transportation and food distribution were most affected, resulting in a general rise in the prices of goods and services. Novelty: The study provides household-level empirical evidence that highlights citizens’ lived socio-economic experiences following subsidy removal. Originality: It contributes to existing literature by directly linking subsidy removal to food inflation, reduced living standards, and poverty escalation using primary data. Conclusion: Fuel subsidy removal has had adverse socio-economic consequences for Nigerian households. Type of Paper: Research article.